City: Civilizing Mask? - Segura Gutiérrez, José Miguel (Cooperativismo & Desarrollo, 2015)
Purpose: The article is a reflection about the way in which the city, as an unfinished expression of the civilizing process, at least in the West, has favored not only the institutionalization of sociocultural, political and economic forms for the benefit of humanity, but has also caused distress, both because of the selfish nature of human beings and their incessant search for better living conditions. Description: From the position of the citizen-person, it shows the fragility with respect to certain forms of administration of human life, that are used to subjectivize people and thereby reveal the complex and problematic social, subjective and cultural reality of the inhabitants. Point of view: It is from the city as a social space that it is possible to detect the tensions among the different individuals who inhabit it, with respect to socio-spatial demarcations of time and consumption. Conclusions: Human life in the city is simply the dramatization of a civilizing process that, in its time, was full of good intentions. The experience of living in a city is not only rational and economic, but also sensorial and very emotional.
Keywords: city; civilization; market; processes of life.